PENDALAMAN NERACA SALDO BAGI SISWA/I SMA KRISTOFORUS 1 - Ferry Adang; Amin Wijoyo; Steven Wiryajaya; Richard Edbert (Jurnal Serina Abdimas, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) program titled Trial Balance Deepening for Students of SMA Santo Kristoforus 1 Jakarta aims to enhance students’ understanding of basic accounting concepts, particularly in preparing trial balances as a crucial part of the accounting cycle. This activity applied an interactive, practice-based learning approach conducted face-to-face, supported by the Kahoot platform for pre-test and post-test evaluations. Through this approach, students were guided to comprehend the relationship between general journals, ledgers, and trial balances, while logically tracing the balance between debit and credit. The results indicated a significant improvement in students’ understanding, as reflected in their post-learning evaluations. Furthermore, the engaging and competitive learning atmosphere encouraged students to participate actively, demonstrate accuracy, and show enthusiasm during the session. This program not only strengthened students’ academic and analytical competencies in accounting but also fostered greater interest in the subject as a discipline relevant to both business and daily life. Overall, the activity represents a concrete implementation of the MBKM initiative, creating an innovative, contextual, and sustainable learning experience that enhances financial literacy among high school students.